2021
DOI: 10.1007/s00223-021-00866-9
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Cartilage Interface and Osteoarthritis

Abstract: This review describes results obtained with tissue from prior studies of equine and human osteoarthritis (OA). The main methods considered are scanning electron microscopy, novel methods in light microscopy and X-ray Micro-tomography. The same samples have been re-utilised in several ways. The tissues described are hyaline articular cartilage (HAC; or substitutes), with its deep layer, articular calcified cartilage (ACC), whose deep surface is resorbed in cutting cone events to allow the deposition of subchond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…Instead, osteochondral junction remodelling results in gradual thinning of the ACC with age, as osteoclasts (known as chondroclasts in cartilage) erode ACC adjacent to SCB, and osteoblasts replace it with bone (Boyde, 2021). Further work by Doube et al (2007) in horses has identified the rate of chondroclastic resorption, as opposed to tidemark linear accretion rate, as the major determinant of ACC thickness in young horses.…”
Section: Matrix Bioactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, osteochondral junction remodelling results in gradual thinning of the ACC with age, as osteoclasts (known as chondroclasts in cartilage) erode ACC adjacent to SCB, and osteoblasts replace it with bone (Boyde, 2021). Further work by Doube et al (2007) in horses has identified the rate of chondroclastic resorption, as opposed to tidemark linear accretion rate, as the major determinant of ACC thickness in young horses.…”
Section: Matrix Bioactivitymentioning
confidence: 99%
“…Highly mineralised infill material is then deposited in the ACC crack and so is extruded into the HAC tear with which it is continuous (Boyde, 2021). HDMPs therefore are not surrounded by tidemark (Boyde et al, 2011).…”
Section: Tidemark Advancementmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, some exceptions to this rule. For example, a thin layer of articular calcified cartilage that is more mineralized than subchondral bone is regularly present in diarthrodial joints of the adult skeleton ( Ferguson et al, 2003 ; Boyde, 2021 ). Persistence of calcified cartilage islands also occurs in long bones of rats and mice due to the lack of bone remodeling in these small mammals ( Bach-Gansmo et al, 2013 ; Jing et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alan Boyde revisits the theme of aberrant mechanical loading, complex tissue interactions, rare diseases, biomarkers and animal models of osteoarthritis in a paper that considers what role the bone-cartilage interface plays in OA [5]. The article and the accompanying and extensive supplementary material are filled with images that should enthral and inform readers.…”
mentioning
confidence: 99%